Optimalisasi Pertumbuhan Panjang dan Ketebalan Miselium Jamur Tiram Putih (Pleurotus ostreatus) Dengan Variasi Komposisi dan Posisi Baglog - Ridwan, Riswan; Jamaluddin, Jamaluddin; Patang, Patang (Agricultural Technology Education Study Program, 2023)
The process of cultivating white oyster needles is quite easy and supported by the raw materials used, which are easy to find at affordable prices. However, inappropriate raw materials and media composition, as well as an inappropriate baglog position will affect the growth of mycelium so that the results in white oyster mushroom cultivation are less than optimal. This study aims to determine the mixture of planting media and the variation of baglog position on the optimal growth of white oyster mushroom mycelium. This research method uses an experimental form with the type of research used is descriptive quantitative. The research design in this study was a factorial randomized block design. The results of this study were the concentration with 25% corn flour was the treatment with the best mycelium length, namely the final mycelium length average of 17.45 cm. The treatment with 35% corn flour was the treatment with the best mycelium thickness. The position of placing the baglog for growing white oyster mushroom was not significantly different from the growth of mycelium, this was because at the time of laying the baglog the position of the baglog was spaced and not piled up.